Perioperative fluid and electrolyte management in surgical neonates - Peters, Nitin James; Dogra, Shivani; Yaddanapudi, Sandhya; Mahajan, Jai Kumar (Journal of Neonatal Surgery, 2023)
Neonates with surgical conditions may experience significant electrolyte abnormalities and dehydration of varying degrees. Increased awareness of perioperative hyponatremia and its associated morbidity has led to a shift in Pediatric fluid guidelines favoring the use of isotonic fluids. However, there is a lack of evidence-based guidelines for neonatal perioperative fluid administration, resulting in the extrapolation of fluid management principles from adults and children. This article reviews perioperative neonatal fluid management.